2016
DOI: 10.1080/15476286.2016.1227904
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role and clinical implication of human exonic circular RNA

Abstract: Circular RNA from backspliced exons (or exonic circular RNA, circRNA) is a type of covalently closed noncolinear RNA that was recently rediscovered in eukaryotes. Although circRNAs are often expressed at low levels, emerging evidence indicates that many circRNAs are linked to physiological development and various diseases. Notably, circRNAs have been shown to serve as oncogenic stimuli or tumor suppressors in cancer. circRNAs may regulate gene expression through different mechanisms. In addition, circRNAs have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 58 publications
1
79
0
Order By: Relevance
“…Functions of circRNAs remain largely unclear. CircRNAs may be generated from exonic or intronic sequence and function as modifiers of parental gene expression . In the current study, we sequenced four circRNAs of interest following a microarray screening.…”
Section: Discussionmentioning
confidence: 99%
“…Functions of circRNAs remain largely unclear. CircRNAs may be generated from exonic or intronic sequence and function as modifiers of parental gene expression . In the current study, we sequenced four circRNAs of interest following a microarray screening.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of circRNAs is tissue-specific, and most circRNAs exhibit differential expression patterns in different species, tissues and cells (5,6). The majority of circRNAs are <1,500 nucleotides in length, with an average length of ~500 nucleotides (7,8). Several circRNAs have been identified to be closely related to the recurrence and prognosis of bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…circRNAs are single‐stranded covalently closed transcripts. Microarray or RNA sequencing analysis showed that circRNAs are widely dysregulated in cancers and potentially play suppressive or oncogenic roles in multiple cancers . circRNAs could be enriched and stable in exosomes.…”
Section: Oncogenic Roles Of Exosomes In Cancermentioning
confidence: 99%
“…Microarray or RNA sequencing analysis showed that cir-cRNAs are widely dysregulated in cancers and potentially play suppressive or oncogenic roles in multiple cancers. 112 circRNAs could be enriched and stable in exosomes. Exosomes containing tumor-specific circRNAs are released by tumor cells.…”
Section: Exosomal Mirnas Circrnas and Lncrnas In Cancersmentioning
confidence: 99%